Marketing Strategy of Service Products in Efforts to Increase Revenue at PAUD Kartika Pradana, Malang City - Meriana Norince Bora; Agus Dwi Sasono; Yuni Setyawati; Nur Ida Iriani (International Research & Development for Human Beings (IRDH), 2026)
This research discusses the marketing strategy of service products implemented by PAUD Kartika Pradana in Malang City as an effort to increase institutional income. In an era of increasingly tight competition in the early childhood education sector, institutions are required to understand market needs and develop targeted marketing strategies. The main focus of this research is how the implemented marketing strategies can attract public interest and lead to an increase in student enrollment. This study uses a descriptive qualitative method with data collection techniques through direct observation, in-depth interviews with the PAUD management, and documentation study. The results show that PAUD Kartika Pradana relies on the 7P marketing mix approach: product (educational services), competitive pricing, strategic location, active promotion through social media and local communities, competent human resources, structured service processes, and adequate physical facilities. This combination of strategies significantly contributes to building trust among parents and encouraging them to enroll their children. The findings indicate that PAUD Kartika Pradana implements a service marketing strategy based on the 7P approach (Product, Price, Place, Promotion, People, Process, and Physical Evidence). Dominant promotional strategies include word-of-mouth marketing, use of social media, and collaboration with local communities. This research concludes that implementing an appropriate service marketing strategy can be an effective solution to enhance the competitiveness and income of educational institutions.